2018
DOI: 10.1007/s10840-018-0398-z
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia care in Africa

Abstract: Data on cardiovascular disease, including arrhythmias, in Africa is limited. However, the burden of cardiovascular disease appears to be on the rise. Recent global data suggests an increase in atrial fibrillation rates despite declining rates of rheumatic heart disease. Atrial fibrillation is also associated with increased mortality in Africa. Current management with medical therapy is sub-optimal and ablation procedures, inaccessible. Atrial fibrillation is also an independent risk factor for death in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The best predictor of ROSC was a shockable rhythm (VT/VF), followed by PEA, with asystole having the worse outcomes [58,65]. Multiple surveys in SSA have demonstrated that even clinicians including physicians do not have adequate basic life support (BLS) and advanced cardiac life support (ACLS) training (about half of those surveyed), and the majority are unable to operate an automated external defibrillator (AED) [13,97,98]. In South Africa where EMS services are available, overall knowledge and skill performance of CPR is still well below standard by EMS personal with only 25% of the required standards met [99].…”
Section: Cardiopulmonary Resuscitation (Cpr)mentioning
confidence: 99%
See 1 more Smart Citation
“…The best predictor of ROSC was a shockable rhythm (VT/VF), followed by PEA, with asystole having the worse outcomes [58,65]. Multiple surveys in SSA have demonstrated that even clinicians including physicians do not have adequate basic life support (BLS) and advanced cardiac life support (ACLS) training (about half of those surveyed), and the majority are unable to operate an automated external defibrillator (AED) [13,97,98]. In South Africa where EMS services are available, overall knowledge and skill performance of CPR is still well below standard by EMS personal with only 25% of the required standards met [99].…”
Section: Cardiopulmonary Resuscitation (Cpr)mentioning
confidence: 99%
“…Nonetheless, arrhythmias are probably underdiagnosed in SSA due to lack of equipment and expertise [10]. Few informative surveys and reviews on the status of arrhythmia services in Africa have revealed severe deficiencies in healthcare systems and arrhythmia specialists [9,[11][12][13][14]. However, a detailed description of clinical arrythmia entities in SSA is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, these estimates may be skewed by the effects of sampling, with known variability in health care infrastructure and services among sub-Saharan African countries and poor health-seeking behavior. 4 Notably, AF patients in sub-Saharan Africa tend to be younger and with higher mortality rates due to poor health care access and suboptimal therapy, 3 and screening may help to identify individuals who can benefit from risk factor modification and medical therapy to reduce the burden of disease and associated morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant variation in the prevalence of AF reported across different countries in Africa, and estimates may be skewed by poor health-seeking behaviors and limited access to diagnostic equipment. 4 Better understanding of the cardiovascular risk factor profile in these regions can help guide preventive and management strategies. Given the relative scarcity of AF epidemiology data from sub-Saharan African regions, we undertook the TEFF-AF (The hEart oF Ethiopia: Focus on Atrial Fibrillation) screening study to characterize the prevalence of AF and associated risk factor profile in semi-rural south-central Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The incidence of ES in Sub-Saharan Africa (SSA) has not been well documented as ventricular arrhythmias are often under-recognized and undertreated in this sub-region. 2 However, in Western countries, an incidence of 4% to 40% has been reported in patients with implantable cardioverter defibrillators (ICDs), with a high mortality rate of up to 14% within 48 hours. 1 There is no clear consensus diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%